Liberating loan shark victims: The collaborative role of BAZNAS, Pesantren, and Cianjur Social Services in zakat-based rehabilitation - Hadiyanto, Redi; Pusvisasari, Lina; Athoillah, Mohamad Anton (Journal of Islamic Economics Lariba, 2026)
IntroductionLoan shark predation traps financially vulnerable households in recurring debt, weakens family welfare, and undermines community stability. Conventional interventions often provide temporary debt relief without addressing the economic, legal, psychological, and spiritual conditions that cause victims to return to predatory lending. Productive zakat offers a potential instrument for social rehabilitation when combined with community trust, legal protection, and sustainable economic empowerment.ObjectivesThis study examines the collaborative roles of the National Zakat Agency of Cianjur, pesantren, and the Cianjur Social Service Agency in rehabilitating loan shark victims through zakat-based programs. It analyzes the division of institutional responsibilities, implementation mechanisms, synergistic interactions, program outcomes, and challenges affecting long-term sustainability.MethodThe study employed an emergent qualitative multiple-case design in Cugenang, Cipanas, Pacet, and Cikalong Kulon, Cianjur Regency, Indonesia. Data were collected over six months through semi-structured interviews, longitudinal field observations, and document analysis. The initial participants comprised twenty-four representatives of the National Zakat Agency, pesantren leaders and administrators, social-service personnel, and beneficiary household heads. Data were analyzed through abductive thematic analysis, constant comparison, maximum-variation sampling, and deviant-case analysis.ResultsThe findings reveal a four-stage rehabilitation process consisting of victim identification and verification, core intervention, mentoring and monitoring, and sustainability support. The National Zakat Agency provided productive zakat capital and Sharia financial education. Pesantren facilitated victim identification, religious counseling, spiritual commitment, and community trust. The Social Service Agency delivered legal mediation, administrative assistance, and access to social protection. Debt mediation succeeded in more than eighty percent of cases, while all beneficiaries-initiated microenterprises using productive assets. Participants also reported reduced anxiety, restored dignity, and stronger social belonging. However, approximately thirty percent of businesses stagnated after twelve to eighteen months.ImplicationsSustainable rehabilitation requires formal coordination, advanced business mentoring, long-term monitoring, and institutional mechanisms that reduce dependence on individual local leaders.Originality/NoveltyThis study introduces a community-embedded tripartite model that integrates productive zakat, religious authority, and government social protection. It expands zakat from consumptive assistance into a transformative instrument for debt liberation, economic independence, spiritual recovery, and social justice.